2002
DOI: 10.1002/jcp.10086
|View full text |Cite
|
Sign up to set email alerts
|

COX‐dependent and ‐independent pathways in bradykinin‐induced anion secretion in rat epididymis

Abstract: Lysylbradykinin (LBK) added to the apical or basolateral side of cultured rat epididymal monolayers stimulated a rise in short-circuit current (Isc) due to anion secretion. The concentration-response relationships for the apical and basolateral applications have EC50 value of 0.001 microM. The responses to apical or basolateral application of LBK were blocked by WIN64338, a specific B2 receptor antagonist, but not by Des-Arg9,[Leu8]-BK, a specific B1 receptor antagonist, indicating that the LBK effects were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…Thus, a large part of the UDP-mediated stimulation of Cl -secretion apparently occurs through the generation of prostaglandins and a subsequent stimulation of an epithelial cAMP increase. In analogy to other epithelial organs where prostaglandin release was shown to originate form epithelial cells, we suggest that a similar phenomenon is true in colonic mucosa (26,30). Our results, however, do not rule out whether, in addition to a "direct" epithelial effects, other subepithelial cells (e.g., immunocytes) contribute in an "indirect" way to the observed UDP-stimulated secretion.…”
Section: Discussionsupporting
confidence: 47%
“…Thus, a large part of the UDP-mediated stimulation of Cl -secretion apparently occurs through the generation of prostaglandins and a subsequent stimulation of an epithelial cAMP increase. In analogy to other epithelial organs where prostaglandin release was shown to originate form epithelial cells, we suggest that a similar phenomenon is true in colonic mucosa (26,30). Our results, however, do not rule out whether, in addition to a "direct" epithelial effects, other subepithelial cells (e.g., immunocytes) contribute in an "indirect" way to the observed UDP-stimulated secretion.…”
Section: Discussionsupporting
confidence: 47%
“…Such effects result in rapid modulation of epithelial function by osmolality, just as in the MTs, but the MTs respond to changes in osmolality in a fundamentally different way then has been reported for other epithelia. It is intriguing to note the numerous examples of secretory epithelia that are under the control of biogenic amines and other hormones (2,10,11,20,30,47,52). The current data raise the possibility that some of these signaling pathways might also be modulated by osmolality just as is tyramine signaling in the MTs.…”
Section: Discussionmentioning
confidence: 85%
“…As with other ion channels on the membrane, CFTR was controllable by pharmacological agents, such as noradrenalin [1], lysylbradykinin (LBK) [9], and PACAP [2]. However, the physiological functions of CFTR and CLCAs that are regulated by CCH have not been shown.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies reported that various neurohormonal agents, including adrenaline, bradykinin, gastrin-releasing peptide, and prostaglandin E 2 and F 2a , are effective stimulants of electrogenic transport across epididymal epithelia of a number of species [9,10]. The cellular mechanisms, e.g., transporters and ion channels, underlying these responses have been elucidated, but the mechanisms of CCH-induced Cl À secretion by epididymis has not been shown.…”
Section: Introductionmentioning
confidence: 99%